2016
DOI: 10.1080/17429145.2016.1262914
|View full text |Cite
|
Sign up to set email alerts
|

Bio fertilizers and zinc effects on some physiological parameters oftriticaleunder water-limitation condition

Abstract: In order to study bio fertilizers and zinc effects on some physiological parameters of triticale under a water-limitation condition, a factorial experiment was conducted based on randomized complete block design with three replications in 2014 and 2015. Experimental factors consisted of three irrigation treatments [normal irrigation (W 0 ); moderate water limitation (W 1 ) and severe water limitation (W 2 )]; four bio fertilizers' levels [(no bio fertilizer (F 0 ), application of mycorrhiza (F 1 ), plant-growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 46 publications
3
18
0
3
Order By: Relevance
“…It is noteworthy in the present examination that the integration of PGPR (soil application) alongside SA (foliar application) greatly improved the yield-related traits and wheat productivity possibly through collaboration with auxin and/or cytokinin synthesis, the increment of cell division and photosynthesis [40]. The SA further helped the PGPR inoculated plants to improve the physiological traits and photosynthetic activity through enhanced CO 2 assimilation rates due to increased stomatal conductance, relative water content, and chlorophyll content under water deficit [9,41]. Furthermore, the integration between PGPR and SA reduced the proline content that accumulates under water deficit conditions resulting in osmotic adjustment, free radical scavenging, and stabilization of subcellular structures in plant cells and mitigation of the harmful impacts of water deficit [42].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is noteworthy in the present examination that the integration of PGPR (soil application) alongside SA (foliar application) greatly improved the yield-related traits and wheat productivity possibly through collaboration with auxin and/or cytokinin synthesis, the increment of cell division and photosynthesis [40]. The SA further helped the PGPR inoculated plants to improve the physiological traits and photosynthetic activity through enhanced CO 2 assimilation rates due to increased stomatal conductance, relative water content, and chlorophyll content under water deficit [9,41]. Furthermore, the integration between PGPR and SA reduced the proline content that accumulates under water deficit conditions resulting in osmotic adjustment, free radical scavenging, and stabilization of subcellular structures in plant cells and mitigation of the harmful impacts of water deficit [42].…”
Section: Discussionmentioning
confidence: 91%
“…These studies are in line with [13], who reported the contributory role of the integration between bacterium inoculum and salicylic acid as foliar spraying in increasing cell elongation, which owing to water flow from the xylem to the adjacent elongation cells, results in strengthened mitosis and cell enlargement leading to an increase in yield-related traits and productivity. It could be summarized that PGPR and its combination with SA increased chlorophyll content in leaves could be attributed to higher availability of nutrients and increased organic matter in the rhizosphere leading to increases in 1000-grain weight, number of grains spike −1 , and number of spikes m −2 due to the pivotal impact of chlorophyll on photosynthetic activity [41]. Foliar application of SA demonstrated, in the present examination, a better capability of increasing grain and straw yield than soil application of PGPR.…”
Section: Discussionmentioning
confidence: 99%
“…В ряде исследований отмечается торможение скорости фотосинтеза у растений при недостатке цинка, что является следствием изменений и/или нарушений в ФСА Munirah et al, 2015]. Однако все эти данные получены на растениях, находящихся на поздних фазах развития [Alloway, 2004;. В наших исследованиях у опытных проростков замедления скорости фотосинтеза не наблюдалось, несмотря на снижение содержания фотосинтетических пигментов и уменьшение устьичной проводимости (рис.).…”
Section: результаты и обсуждениеunclassified
“…У злаков дефицит цинка в почве вызывает целый ряд изменений в фотосинтетическом аппарате (ФСА), в том числе редукцию хлоропластов, снижение содержания фотосинтетических пигментов, нарушение работы устьичного аппарата, замедление скорости фотосинтеза . Однако указанные признаки дефицита цинка обнаруживаются, как правило, только в фазы кущения или выхода в трубку [Alloway, 2004;. Поэтому большинство имеющихся экспериментальных данных, касающихся влияния недостатка цинка на ФСА, получено именно в эти фазы онтогенеза.…”
Section: Introductionunclassified
“…eing a cross between wheat and rye, triticale combines the high-yield potential of wheat with the biotic and abiotic stress tolerance of rye, making it suitable for production in marginal areas (Badiyal et al, 2014;Arough et al, 2016). The main triticale-growing areas are Belarus, France, Germany and Poland (FAO, 2015;Losert et al, 2017).…”
mentioning
confidence: 99%